Politeness in Requests of Maudy’s Ayunda Talk Shows to Different Genders - Clarissa Gracesella Wahyudi (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
This study was conducted to find out the ways Maudy Ayunda, as the talk show's host, performs requests and responds to Ayu's and Nadiem's requests which have different genders. Also, the analysis was leveled up to the relation of politeness and gender. The main theory used was Watts (2003), focusing on the first-order politeness connected to Indonesian (Javanese) culture. Other supporting theories and studies from Suseno (2003), Kuntjara (2009), and Mills (2003) were used. The method used is a descriptive qualitative approach using utterance/s as the unit of analysis. The findings revealed that Maudy mostly used indirect patterns in conveying the requests and accepted the guests' requests as her response. Several direct patterns were found but could be considered appropriate if analyzed based on the context. Concerning gender, Maudy used more direct patterns to answer Nadiem's requests than Ayu's.Keywords: politeness, first-order politeness, requests, utterance